Imagining Eden: Black theology and the search for paradise - Calloway, Jamall A. (Black lives in the diaspora: past, present, future, 2026)
"Argues that Black literature has functioned as a primary source of theological reflection and reimagining since its beginnings. From slave narratives to twentieth-century poetry and novels-the latter of which is the focus of this book-it has participated in systematic theological discourse and offered as a response to orthodox interpretations what the author calls heretical hermeneutics, a type of irreverent insight that has explored theological thinking in other ways than the canonical. For Black writers, the authoritative and the doctrinal have justified white political sovereignty, and therefore freedom can only be found in the heretical, the blasphemous, and the creative reimagining of theologies and biblical documents. Jamall A. Calloway contends that Richard Wright, James Baldwin, Alice Walker, and Toni Morrison use religious symbolism to depict fully formed Black liberation theologies that address the complexities of religious wonder, theological doctrines, social practices, and communal rituals. All see the Garden of Eden as a unifying center; the author evaluates Wright's fall from Paradise in conversation with Kierkegaard's, Baldwin's opposition to the mortification of the flesh found in St. Paul, Morrison's sexuality compared to St. Augustine's, and Walker's radical notion of a free, living animal in conversation with Catholic theologian Ivone Gebara. In their different ways all four writers offer liberation theologies that return to Eden to explore how Black lives are marked by tragedy and how they can find the human and spiritual qualities needed to persist in the face of it"-- Provided by publisher